Human Resource Development Management In Engineering Study Program - Pilihantoro Pilihantoro; Sowiyah Sowiyah; Riswanti Rini (Program Studi Magister Manajemen Pendidikan, 2022)
Abstrak: Human Resource Development in the Engineering Study Program. This study aims to describe the formulation of human resource development planning (HR) in the Electrical Engineering Study Program at the Sumatra Institute of Technology with a higher education administration management function approach that aims to improve superior learning services. The problem raised is the lack of synergy between the fields of learning and the work needs of graduates. The focus of the research is the indicator of permanent lecturers according to the adequacy of the value of increasing the accreditation of Study Programs by BAN-PT in the achievement of the superior category in 2024 as an effort to qualify themselves for the realization of the excellence of Study Programs. The research method using the approach model is descriptive qualitative. Minimum quality standards in scanning research data based on the Strategic Plan. The results of the study indicate that there is insufficient adequacy of lecturers on the Doctoral and Lecturer indicators according to the accreditation assessment. Efforts to improve it require the strength of individuals who have contributed to the achievement of study program accreditation to manage internal quality clusters in utilizing the potential opportunities of existing human resources. In conclusion, it is necessary to manage human resources programs that focus on improving quality according to the evaluation of a higher accreditation value. Keywords: Human Resource Management (HR), higher education organizations, Accreditation Quality Standards